The Legal natural to the contract buy the Commercial rights (Factorrring( - Mohammed Khudhur AL saeedey, Bassim (Journal of College of Education, 2020)
the contract for the purchase of commercial rights or factoring is based on the idea that the fixed rights in the debtor’s account in the event that the creditor is unable to collect them himself, either because it is deferred or that its collection needs financial expenses or procedures that the debtor cannot afford, or that the creditor person does not have sufficient time to collect all his rights in the debt based on the multiplicity, difference and divergence of places of fulfillment. Therefore, this creditor shall sell his fixed rights in the hands of a city to a competent institution that will collect these rights within its time limits after paying its accelerated value to the creditor in exchange for an agreed between them, which may be part of the value of the right. The factoring contract provides interest on both sides, it provides the creditor with the right deferred from the institution after it was deferred by the debtor away from obstacles in the way of its completion, and also provides the foundation of the foundation from obtaining the right in full or in return for the purchase of the right from its owner. For all these reasons, the Factoring contract has become a widespread contract in the commercial environment because of its benefits not in the interest of the enterprise